Exploring the concept of paratranslation and its implementation in El album mexicano's version of The flowers personified - Correa Larios, Olivia (2020)
El álbum mexicano was an illustrated literary magazine edited by the printer Ignacio Cumplido that circulated in Mexico during 1849. Each number of the magazine included an illustration taken from Les fleurs animées (The flowers personified), an illustrated book published in France in 1847 by the illustrator and cartoonist Jean Ignace Isidore Grandville. The book dealt with the theme of values and the role of women. This book became an inspiration to develop a discourse about women through translations, abstracts, paraphrases and adaptations of the original text but also through new stories and essays that go beyond the translation process. Based on these illustrations and texts, this work proposes an exploration of the notion of paratranslation through the analysis of verbal and nonverbal paratextual elements linked to the source text and, mostly to the target text. Using the conceptual framework developed by Yuste Frías, the aim of this work is to demonstrate the applicability of the notion of paratranslation to the adaptation of texts and images for various target languages and cultures.